FEATURES OF LIFE-MEANING ORIENTATIONS OF YOUNG ADULTS WITH DIFFERENT LEVELS OF REFLEXION - Yulia I. Popova (Образование и наука)
The purpose of the research is to establish specifics of lifemeaning orientations of young adults with different levels of reflexion. Methods. The methods involve empirical data collection methods, mathematical methods of statistics (nonparametric Mann – Whitney U test is used for comparing two independent samples and assessing significance of their differences; nonparametric Kruskal – Wallis H test is used for assessing the impact of reflexion level on life-meaning orientations), descriptive statistics. 45 girls and 15 boys in the age range of 21–22 took part in the research. Results. Analysis of the data led to conclusion that there is non-linear connection between the level of reflexion development and life-meaning orientations of young adults. This connection may be seen as reflexion’s influence on lifemeaning orientations, which consists of gender-specific and gender-nonspecific features. Gender-nonspecific features of this connection are: level of retro-reflexion influences such life-meaning orientations as self-contentment, self-productivity and assessment of individual’s past; level of situational reflexion influences such life-meaning orientations as ability of self-regulation and image of individual’s strength and freedom; level of prospective-reflexion influences such life-meaning orientations as assessment of future success and the ability to clearly see life goals. Gender-specific features of this connection is inter-reflexion influence on life-meaning orientations. Girls with high level of inter-reflexion also demonstrate clear understanding or personal self-control, assessment of personal freedom, and awareness of life goals. Scientific and practical significance. Further research and analysis of those features may help deeper understanding the connection between reflexion as a factor of inward self-regulation, and life-meaning orientations as a factor of outward regulation of individual activity.